2020
DOI: 10.1111/jnc.14963
|View full text |Cite|
|
Sign up to set email alerts
|

microRNA‐9‐5p alleviates blood–brain barrier damage and neuroinflammation after traumatic brain injury

Abstract: The level of microRNA‐9‐5p (miRNA‐9‐5p) in brain tissues is significantly changed after traumatic brain injury (TBI). However, the effect of miRNA‐9‐5p for brain function in TBI has not been elucidated. In this study, a controlled cortical impact model was used to induce TBI in Sprague–Dawley rats, and an oxygen glucose deprivation model was used to mimic the pathological state in vitro. Brain microvascular endothelial cells (BMECs) and astrocytes were extracted from immature Sprague–Dawley rats and cocultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 48 publications
4
34
0
Order By: Relevance
“…1I ). These results are partly consistent with those from our previous research 20 . Unexpectedly, however, we found that when the miRNA-9-5p oligomers were injected only at 14 days after CCI, although the level of miRNA-9-5p in injured brain tissues was similar to that observed with DI (Fig.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…1I ). These results are partly consistent with those from our previous research 20 . Unexpectedly, however, we found that when the miRNA-9-5p oligomers were injected only at 14 days after CCI, although the level of miRNA-9-5p in injured brain tissues was similar to that observed with DI (Fig.…”
Section: Resultssupporting
confidence: 94%
“…Therefore, clarifying the role of miRNAs after TBI may be helpful for formulating treatment strategies in the future. Our previous studies also verified that upregulation of miR-9-5p in the acute phase after TBI can reduce the inflammatory response and BBB destruction, thus promoting neurological function recovery 20 . However, whether the upregulation of miR-9-5p has the same neuroprotective role in the chronic phase after TBI remains unknown.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations